2013
DOI: 10.1377/hlthaff.2012.0913
|View full text |Cite
|
Sign up to set email alerts
|

Seven Million Americans Live In Areas Where Demand For Primary Care May Exceed Supply By More Than 10 Percent

Abstract: The Affordable Care Act's expansion of insurance coverage is expected to increase demand for primary care services. We estimate that the national increase in demand for such services will require 7,200 additional primary care providers, or 2.5 percent of the current supply. On average, that increased demand is unlikely to prove disruptive. But when we examined how this increased demand will be experienced in different areas of the country, we found considerable variability: Seven million people live in areas w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 14 publications
1
71
1
Order By: Relevance
“…3 On the other hand, our finding of support for the ACA by future physicians who are considering medical specialties is reassuring in light of predicted physician shortages due to expanded insurance coverage. 29 Students' self-reported level of understanding in our sample was high (75 %), much higher than in our 2011 regional study in which only 48 % of students indicated an understanding of the ACA. 11 There may be several reasons for this finding, including the substantial media coverage the ACA has received since its inception, 30 a natural interest in the topic by students, and, perhaps, new health policy education initiatives across the country.…”
Section: Discussioncontrasting
confidence: 68%
“…3 On the other hand, our finding of support for the ACA by future physicians who are considering medical specialties is reassuring in light of predicted physician shortages due to expanded insurance coverage. 29 Students' self-reported level of understanding in our sample was high (75 %), much higher than in our 2011 regional study in which only 48 % of students indicated an understanding of the ACA. 11 There may be several reasons for this finding, including the substantial media coverage the ACA has received since its inception, 30 a natural interest in the topic by students, and, perhaps, new health policy education initiatives across the country.…”
Section: Discussioncontrasting
confidence: 68%
“…Although one recent state-level analysis suggested that the current physician workforce supply in both primary care and most specialties is sufficient to meet future demand (Glied & Ma, 2015), the analysis assumed an increase in physician workload and did not examine potential variation in supply and demand across local areas within states. Indeed, a within-state small area analysis examining the impact of ACA reforms using the same source of data suggested that about 44 million Americans live in areas where the expected increase in demand for primary care will exceed 5% and almost seven million reside in areas where the expected demand will increase by more than 10% (Huang & Finegold, 2013). The Health Resources and Services Administration (HRSA) estimates that the supply of primary care physicians (PCPs) will not meet future demand, with a projected shortage of approximately 20,400 full-time equivalent physicians by 2020 (HRSA, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, among the 24 states predicted to have an increase in demand for primary care providers above the national average due to the implementation of the ACA, 17 have restrictive NP SOP regulations (Huang & Finegold, 2013). To assist state policy makers in making evidence-based decisions on legislative reforms concerning the expansion of the NP role in health care delivery, we conducted a systematic review on the impact of state NP SOP regulations on health care delivery, specifically focusing on the following three key issues: (a) NP workforce, (b) access to care and health care utilization, and (c) health care costs.…”
Section: Introductionmentioning
confidence: 99%
“…Hofer, Abraham, and Moscovice (2011) point out that there was already a shortage of primary care doctors before the ACA and suggest that the increased demand from the ACA could increase the shortages. Huang and Finegold (2013) find that certain areas will be hit hard by an increase in demand. They estimate that 7 million people live in areas where demand for primary care may exceed supply by 10 percent after the ACA.…”
Section: Shared Medical Resourcesmentioning
confidence: 99%